Understanding triglyceride glucose-body mass index: implications for diabetes and cardiovascular disease management - Zhou, Shunping; Guo, Rong (Frontiers in Endocrinology, 2025)
This article focuses on the Triglyceride-Glucose Body Mass Index (TyG-BMI) in diabetes and its associated cardiovascular complications. It elaborates on the basic concepts, current clinical practices, technological advancements, controversies, challenges, and future directions related to TyG-BMI. By integrating the findings from numerous studies, we aimed to provide a comprehensive understanding of the role of TyG-BMI in diabetes and cardiovascular disease research, diagnosis, and treatment, highlighting its significance and potential for improving the management of diabetic cardiovascular health.